Design of D-Amino Acids SARS-CoV-2 Main Protease Inhibitors Using the Cationic Peptide from Rattlesnake Venom as a Scaffold - Eberle, Raphael J.; Gering, Ian; Tusche, Markus; Ostermann, Philipp N.; Müller, Lisa; Adams, Ortwin; Schaal, Heiner; Olivier, Danilo S.; Amaral, Marcos S.; Arni, Raghuvir K. [UNESP]; Willbold, Dieter; Coronado, Mônika A. (MDPI, 2022)
The C30 endopeptidase (3C-like protease; 3CLpro ) is essential for the life cycle of SARS-CoV-2 (severe acute respiratory syndrome-coronavirus-2) since it plays a pivotal role in viral replication and transcription and, hence, is a promising drug target. Molecules isolated from animals, insects, plants, or microorganisms can serve as a scaffold for the design of novel biopharmaceutical products. Crotamine, a small cationic peptide from the venom of the rattlesnake Crotalus durissus terrificus, has been the focus of many studies since it exhibits activities such as analgesic, in vitro antibacterial, and hemolytic activities. The crotamine derivative L-peptides (L-CDP) that inhibit the 3CL protease in the low µM range were examined since they are susceptible to proteolytic degradation; we explored the utility of their D-enantiomers form. Comparative uptake inhibition analysis showed D-CDP as a promising prototype for a D-peptide-based drug. We also found that the D-peptides can impair SARS-CoV-2 replication in vivo, probably targeting the viral protease 3CLpro .
Keywords: 3CLpro; COVID-19; crotamine derivative peptides; D-peptides; inhibitor; main protease; SARS-CoV-2